Activity and MObility UsiNg Technology (AMOUNT) rehabilitation trial – description of device use and physiotherapy support in the post-hospital phase. Issue 24 (20th November 2021) - Hassett, Leanne; van den Berg, Maayken; Weber, Heather; Chagpar, Sakina; Wong, Siobhan; Rabie, Ashley; McCluskey, Annie; Lindley, Richard I.; Crotty, Maria; Sherrington, Catherine
Abstract: Purpose: To describe device use and physiotherapy support in the post-hospital phase of the AMOUNT rehabilitation trial. Methods: We performed an evaluation of the support required for device use by participants randomised to the intervention group who received digitally-enabled rehabilitation in the post-hospital phase ( n  = 144). Intervention, additional to standard rehabilitation, utilised eight digital devices (virtual reality videogames, activity monitors and handheld computer devices) to improve mobility and increase physical activity. Participants were taught to use devices during inpatient rehabilitation and were then discharged home to use the devices for the remainder of the 6-month trial. Physiotherapist-participant contact occurred every 1–2 weeks using a health coaching approach, including technology support when required. Intervention datasheets were audited, and descriptive statistics used to report device use and support required. Results: Participants (mean (SD) age 70 (18) years; 49% neurological health conditions) used an average of 2 (SD 1) devices (98% used an activity monitor). Eight percent of physiotherapy contact included technology support with 30% provided remotely. Support addressed 845 issues categorised under initial set-up and instruction (27%), education and training (31%), maintenance (23%) and trouble-shooting (19%). Conclusion: Digital devices can be used for home-based rehabilitation, but ongoing technology support is essential. Clinical Trials Registry: ACTRN12614000936628 IMPLICATIONS FOR REHABILITATION: Digital device use at home to support long-term management of health conditions is likely to become increasingly important as the need for rehabilitation increases and rehabilitation resources become more limited. Technology support for set-up and ongoing device use is a critical enabler of home-based digital interventions. Health professionals delivering home-based digital interventions require sufficient training and equipment and may need to vary the mode (e.g., home visit vs. telephone or video conference) depending on the technology support required.